Offline and Online Practices for Assembly Language Programming With 8085 Microprocessor - Muramatsu, Kazuhiro (Proceedings of the ... European conference on e-learning (Online), 2022)
The COVID-19 pandemic has meant that distance teaching and learning at educational institutions since 2020 has become common place. The Ministry of Education in Bhutan has taken the initiative to educate students using learning television and Internet-based online education instead of traditional classes. Thus, the Royal University of Bhutan (RUB) and its ten constituent colleges have been swift in transitioning to online teaching through Moodle and varieties of other applications such as ZOOM, Big Blue Button and Google classroom since March 2020. Since then, offline and online blended teaching began at the College of Science and Technology (CST) under RUB in January 2021. In this paper, we focus on offline and online teaching and learning practices for assembly language programming with the 8085 microprocessor. A Zoom meeting is used for the online practical. Firstly, a tutor gives an 8085 assembly program lesson, which is common to both offline and online teaching practices. In the case of the offline practice, students assemble the assembly program into Hexadecimal code, by looking up a table of the 8085 instruction set. Finally, the Hexadecimal code is input and executed on an 8085 microprocessor trainer, and students confirm the output from the trainer. Here, the trainer is a small computer composed of a microprocessor, peripheral/communication interfaces, timer, memory, input device and output device. In the case of the online practice, on the other hand, students input the assembly program directly on a Web-based 8085 microprocessor simulator. We developed an 8085 microprocessor simulator using JavaScript. Then, students confirm the output from the simulator on a Web browser. The students took 6 offline learning practices and 4 online out of a total of 10. According to a questionnaire survey about the comparison of the offline and online practices from the students, they say offline practices are much better than online ones, because direct communication is important to understand the learning contents. We conclude that there is room for improvement in the online teaching methods.